Makna Agama: Studi Komparasi Pemikiran Wilfred Cantwell Smith dan Karen Armstrong - Hasse Jubba; Dian Septi Purnamasari; Rifa Nurul Isnaeni; Prasna Hestu Swasta (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2022)
Thinking and reformulating the meaning of religion is the responsibility of academics and religious people worldwide. Religion, a medium to feel the presence of God, has a strategic role in solving its adherents’ problems. This article seeks to discuss the thoughts of Wilfred Cantwell Smith and Karen Armstrong since their thought have a strong influence on the religious issues for academics and religious scholars in the world. The thoughts of the two figures in religious studies become a source of knowledge to broaden insights and perspectives and a reflections process related to human diversity and religious interpretation. Through literature study, the researchers find that the two figures emphasize that religion is not static but dynamic. It develops along with human interests and needs. However, some other substantial differences provide a gap to discuss in finding a more contextual meaning of religion.